Intra Orbital Foreign Body; A Case Series - Krishnamurthy Ilango; Gopalakrishnan Ravikumar; Senthil Swetha; V. Senthilnathan (TNOA Journal of Ophthalmic Science and Research)
Intra-orbital foreign body (IOFB) refer to foreign objects that penetrate the ocular globe wall and become lodged in the eye. Intra-orbital foreign body vary in nature, anatomical location, size, and shape and sometimes might cause serious threats to vision, some foreign body can be left alone depending on their nature whether it is organic or non-organic, and their chemical nature. This article deals with a case series of intraocular foreign body, their varied presentations, and how the radiological features helped in localization and planning intervention.